Research Study of ROS2 Library and Interface Development for Industrial Robotic Arm Mitsubishi RV2-SDB - Utomo, Eko Budi; Aziz, Mochammad Abdul (Universitas Nurul Jadid, 2025)
This research study is purposed for development the ROS2 library wich provides the ROS2 interface for industrial robotic arm Mitsubishi RV-2SDB. This library for facilitate the important data acces, such as data joint, position, jog mode, error message, and alarm. By utilizing the ROS2, this library designed for integration suport and robot development in simulation of industrial process, as well as wider automation. The use of ROS2 is deployment modularity and scalability, enable to easier integration with existing automation system. Research studies show that this library is able to improve the efficiency and reliability of robot operations, supporting the industrial revolution 4.0 by creating flexible and integrative solutions.